Peek (Polyether Ether Ketone) – A Review Article (Indian Journal of Forensic Medicine & Toxicology, 2020)
This article is aimed to review the applications of Polyether Ether Ketone (PEEK) in dentistry. The evolvingdesire for functions and aesthetics, few drawbacks with existing materials and clinicians shifting theirparadigms towards metal free restorations led space for the metal-free restorations in today’s restorativepractice. PEEK is a polymer based innovative material, that can be used in either fixed or removableprosthetics. This literature review discusses various applications and uses of PEEK.